Circadian disruptions and their role in the development of hypertension - Crowthers, Raymond; Thi Mong Nguyen, Trinh; Martinez, Diana (Frontiers in Neuroscience, 2024)
Circadian fluctuations in physiological setpoints are determined by the suprachiasmatic nucleus (SCN) which exerts control over many target structures within and beyond the hypothalamus via projections. The SCN, or central pacemaker, orchestrates synchrony between the external environment and the internal circadian mechanism. The resulting cycles in hormone levels and Autonomic Nervous System (ANS) activity provide precise messages to specific organs, adjusting, for example, their sensitivity to approaching hormones or metabolites. The SCN responds to both photic (light) and non-photic input. Circadian patterns are found in both heart rate and blood pressure, which are linked to daily variations in activity and autonomic nervous system activity. Variations in blood pressure are of great interest as several cardiovascular diseases such as stroke, arrhythmias, and hypertension are linked to circadian rhythm dysregulation. The disruption of normal day-night cycles, such as in shift work, social jetlag, or eating outside of normal hours leads to desynchronization of the central and peripheral clocks. This desynchronization leads to disorganization of the cellular processes that are normally driven by the interactions of the SCN and photic input. Here, we review autonomic system function and dysfunction due to regulation and interaction between different cardiorespiratory brain centers and the SCN, as well as social, lifestyle, and external factors that may impact the circadian control of blood pressure.